THE FORMULATION OF A COMPETITIVE STRATEGY FOR A GROUP CAN USE THE BCG AND SWOT MATRICES - Indira Ruth Septarini; Gilbert Citra; Felix Yaptanto (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2026)
The food and beverage industry is highly competitive due to the increasing number of business players and changing consumer preferences. This situation requires companies to formulate competitive strategies that are not only oriented toward short-term sales achievements but also focused on long-term business sustainability. This study aims to analyze the current competitive strategy of Bisa Group and to formulate an appropriate long-term competitive strategy using SWOT analysis and the Boston Consulting Group (BCG) Matrix. This research employs a descriptive qualitative approach, using primary data obtained through observation and interviews, and secondary data collected from company documents and relevant literature. SWOT analysis is conducted by developing the Internal Factor Evaluation (IFE) and External Factor Evaluation (EFE) matrices, determining the company’s position in the SWOT quadrant diagram, and formulating strategies based on the SWOT matrix. Furthermore, the BCG Matrix is applied to identify the position of the restaurant brand portfolio based on market growth rate and relative market share. The results indicate that Bisa Group is positioned in Quadrant I of the SWOT diagram, with an IFE score difference of 1.75 and an EFE score difference of 1.62, showing that the company is in a favorable condition and can implement an aggressive growth strategy (SO strategy). The BCG Matrix analysis shows that Sushi Tei and Pepper Lunch are categorized as Stars, while Paradise Dynasty and Marutama Ramen are categorized as Question Marks. The recommended strategy for Stars is to maintain and strengthen market position, whereas Question Marks require growth strategies through market penetration, market development, and product innovation. The proposed action plan is expected to serve as a guideline for Bisa Group in formulating and implementing long-term competitive strategies to improve competitiveness and sales performance.